Public Support for the Single European Currency, the Euro, 1990 to 2011. Does the Financial Crisis Matter? - Felix Roth; Lars Jonung; Felicitas Nowak-Lehmann D. (Lund University, School of Economics and Management, Department of Economics, 2012)
This paper analyses the evolution of public support for the single European currency, the euro, from 1990 to 2011, focusing on the most recent period of financial and sovereign debt crisis. Exploring a huge database of more than half a million observations covering the 12 original euro area member countries, we find that the ongoing crisis has only marginally reduced citizens' support for the euro. This result is in stark contrast to a sharp fall in public trust in the European Central Bank. We conclude that the crisis – at least so far - has hardly dented popular support for the euro while the central bank supplying the single currency has lost sharply in public trust. Thus, the euro appears to have established a credibility of its own – separate from the institutional framework behind the euro.
Keywords: C23; E31; E42; E65; 330; Support for the euro; European Monetary Union; euro area crisis